Immunoglobulin synthesis by an SV-40-induced hamster lymphoma. - Coe, J E (1976)
A transplantable lymphoid tumour induced in Syrian hamsters by SV-40 was shown to synthesize a 7Sgamma2 monoclonal immunoglobulin of the same idiotype was also found in the membrane of the tumour cell. The induction of immunoglobulin synthesizing tumours by SV-40 should be useful for studies on immunoglobulin synthesis, lymphoid cell receptors and tumour immunity.